Sedimentation Process of Rambatan Formation in Larangan Brebes, North Serayu Range, Central Java - Astuti, Bernadeta Subandini; Isnaniawardhani, Vijaya; Abdurrokhim, Abdurrokhim; Sudradjat, Adjat (Indonesian Journal on Geoscience, 2019)
DOI:10.17014/ijog.6.2.141-151Rambatan Formation in the western part of North Serayu Basin, Brebes, Central Java, comprises generally flysch facies of turbidite sediments deposited in a deep marine environment. This formation is equivalent to Merawu Formation found in the eastern part of the basin and deposited in the environment of tidal flat to subtidal. The turbidite sediments were highly controlled by a rapid downward movement taking place continuously during Early to Late Miocene. The variation of the depositional environment has been the object of this research which aims to understand the sedimentation process of Rambatan Formation in this type locality with a modern turbidite approach. Rambatan Formation was deposited in N13-N19, as a deep marine sediment channel, turbidite, and deep marine tidal zone. The sedimentation was affected by gravity flow and contourite. The sediments on N13-N14 were marked by turbidite sediments until Middle N17. The sediment supply increased on Middle N17, as a sediment filler on a channel marked by contourite mud layer (muddy slump) and debris flow, with sources from the north. The increase of sediment supply was followed by an environmental transformation from a deep marine channel into deep marine tidal area. In N19, the sediments were redeposited as turbidite sediment, starting with debris flow in Middle N18.